2016
DOI: 10.1093/mnras/stw1300
|View full text |Cite
|
Sign up to set email alerts
|

The star formation history and accretion-disc fraction among the K-type members of the Scorpius–Centaurus OB association

Abstract: We present results of a spectroscopic survey for new K-and M-type members of ScorpiusCentaurus (Sco-Cen), the nearest OB Association (∼100-200 pc). Using an X-ray, proper motion and color-magnitude selected sample, we obtained spectra for 361 stars, for which we report spectral classifications and Li and Hα equivalent widths. We identified 156 new members of Sco-Cen, and recovered 51 previously published members. We have combined these with previously known members to form a sample of 493 solar-mass (∼0.7-1.3 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

62
431
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 368 publications
(496 citation statements)
references
References 155 publications
(247 reference statements)
62
431
3
Order By: Relevance
“…However, both explanations still require the distributed population to be older than the concentrated disk-hosting population, indicating that Taurus is a long-lived structure that has produced multiple generations of comoving cospatial star formation, in analogy to the Sco-Cen OB association (Pecaut & Mamajek 2016). The measurement of stellar ages is fraught with uncertainty, due to a combination of measurement errors, unrecognized systematic uncertainties like multiplicity and excesses, and possibly even fundamental scatter in the properties of stars as a result of different assembly histories, rotation rates, or magnetic field strengths (e.g., Hartmann et al 1997;Baraffe & Chabrier 2010;Somers & Pinsonneault 2015a;Feiden 2016).…”
Section: Lithium and The Age(s) Of The Distributed Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, both explanations still require the distributed population to be older than the concentrated disk-hosting population, indicating that Taurus is a long-lived structure that has produced multiple generations of comoving cospatial star formation, in analogy to the Sco-Cen OB association (Pecaut & Mamajek 2016). The measurement of stellar ages is fraught with uncertainty, due to a combination of measurement errors, unrecognized systematic uncertainties like multiplicity and excesses, and possibly even fundamental scatter in the properties of stars as a result of different assembly histories, rotation rates, or magnetic field strengths (e.g., Hartmann et al 1997;Baraffe & Chabrier 2010;Somers & Pinsonneault 2015a;Feiden 2016).…”
Section: Lithium and The Age(s) Of The Distributed Populationmentioning
confidence: 99%
“…The mere existence of past generations of star formation would resolve the ongoing debate of molecular cloud lifetimes (e.g., Hartmann et al 2001;Krumholz & Tan 2007;Murray 2011;Federrath 2015), as kinematically related clouds must have existed since the first generation. Studies of nearby OB associations, most notably Scorpius-Centaurus, are revealing that age gradients and significant age spreads do indeed exist on scales of tens of parsecs (e.g., Pecaut & Mamajek 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Our list of LCC members is based on previous surveys of this region (De Zeeuw et al 1999;Preibisch & Mamajek 2008;Song et al 2012;Pecaut & Mamajek 2016) and consists of 369 stars. In the following, we estimate the current density of stars around the planetary system and its evolution in time.…”
Section: Appendix A: Ad Hoc Force To Account For Type II Migrationmentioning
confidence: 99%
“…Daemgen et al (2015) found that this star, together with several other objects known as bona-fide Taurus members, has similar space position and kinematics to those of the Taurus star forming region, but also shows evidence of a distinctly older age. They proposed an age of about 20 Myr for what is now called the Taurus-Ext Association (see Appendix A in Daemgen et al 2015, and references therein) from comparison of Lithium EW with that of the oldest Sco-Cen groups (Pecaut & Mamajek 2016). Such proposed age for the group is at the young edge of our age range.…”
Section: Stellar Agementioning
confidence: 89%